Bungkus or masak?: an analysis of foodways and consumption habits of Malaysian muslims during ramadan under COVID-19 - Simon, Jillian (2021)
As Malaysia struggles with the COVID-19 crisis, this study is set to uncover the impacts of the pandemic on the largest majority of its population, Muslims. In the month of Ramadan, food, community, and prayer are the essences of the month-long celebration. However, due to physical distancing measures, this was seen to have been a challenge. Hence, this research aims to explore and answer (1) How Malaysian Muslims foodways and diets are changed during Ramadan under the Movement Control Order; (2) What influences their consumption habits during this unique Ramadan season? and, (3) What are the tactics involved to overcome physical distance and produce commensality among Malaysian Muslims?. Discourse analysis on 10 food diaries as well as on food related posts on social media, complemented by data derived from an online survey of 305 respondents reveals food as an actant with the agency to produce communal connections. This paper uses Bruno Latour’s Actor-network theory to ignite the connections between food and Ramadan practitioners, from production to distribution as well as consumption, it shows how food enabled the possibility of creating community connections during Ramadan. Moreover, by looking at food and foodways under a pandemic it unpacks conversations around social inequality, food habits, and food insecurity that will be discussed by using Pierre Bourdieu’s concept of field and capital. Thus, this study shows how food is the binding force in a distant Ramadan season.